Activation of autophagy and IL-10 production are regulated by Jun N-terminal kinase 1 and 2 and p38 mitogen activated protein kinase signaling pathways during Talaromyces marneffei infection within dendritic cells. (February 2020) - Chen, Renqiong; Ji, Guangquan; Ren, Hong; Liu, Zhonglun; Feng, Shan; Zhang, Tingting; Xi, Liyan; Li, Xiaoming
Abstract: Previous study have shown that Talaromyces marneffei ( T. marneffei ) induced activation of autophagy. Therefore, we explore signaling pathway that regulates activation of autophagy by intracellular signaling mechanisms during T. marneffei infection. Further, we examine c-Jun N-terminal kinase 1 and 2 (JNK1/2) and p38 signaling pathways that regulate IL-1β and IL-10 production and activation of autophagy during T. marneffei infection in human dendritic cells (DCs). We found that T. marneffei induced activation of JNK1/2 and p38 in human DCs. Furthermore, the inhibition of JNK1/2 and p38 increased activation of autophagy and decreased the replication of T. marneffei in T. marneffei -infected human DCs. Moreover, IL-1β secretion in T. marneffei -infected human DCs was dependent on JNK1/2 and autophagy pathways, whereas IL-10 secretion was dependent on JNK1/2, p38 and autophagy pathways. These data suggest that JNK1/2 and p38 pathways play critical roles in activation of autophagy, the multiplication of T. marneffei and subsequent cytokine production during T. marneffei infection. Highlights: Activation of JNK1/2 and p38 in DCs following stimulation with T. marneffei . IL-1β and IL-10 release in DCs infected with T. marneffei . JNK1/2 and p38 is required for T. marneffei -induced activation of autophagy. Role of JNK1/2, p38 and autophagy in IL-1β and IL-10 secretion in T. marneffei -infected DCs. Effect of JNK1/2, p38 and autophagy on intracellular replication of T. marneffei in DCs.